2017
DOI: 10.1164/rccm.201609-1862oc
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Air Pollution and Daily Mortality. A Nationwide Analysis in 272 Chinese Cities

Abstract: This nationwide investigation provided robust evidence of the associations between short-term exposure to PM and increased mortality from various cardiopulmonary diseases in China. The magnitude of associations was lower than those reported in Europe and North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
389
4
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 616 publications
(442 citation statements)
references
References 35 publications
46
389
4
3
Order By: Relevance
“…The use of a large city-wide population-based database in this study helped ensure the representativeness and generalizability of our findings. Our findings were supported by a recent national study done in 272 cities in China that reported significant effects of PM 2.5 on mortality [8].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The use of a large city-wide population-based database in this study helped ensure the representativeness and generalizability of our findings. Our findings were supported by a recent national study done in 272 cities in China that reported significant effects of PM 2.5 on mortality [8].…”
Section: Discussionsupporting
confidence: 90%
“…In China, the number of COPD cases increased from 32.4 million in 1990 to 54.8 million in 2013 [3]. Research has provided compelling evidence linking ambient air pollution to COPD risk [4][5][6][7][8]. Ambient fine particulate matter (PM 2.5 , particulate matter ≤2.5 μm in aerodynamic diameter) has been a leading cause of global burden of disease, accounting for an estimated 4.2 million deaths and 103.1 million disability-adjusted life-years in 2015 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Planning Statistical Yearbook 2018. 2,3 We estimate that improved air quality during the 42 quarantine period avoided a total of 8911 [95 confidence interval (CI): 6950, 10866] NO 2 -related 43 . CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: As Of March 14 2020 New Confirmed Covid-19 Cases In Chinamentioning
confidence: 99%
“…A nationwide time-series analysis done in 272 cities between 2013 and 2015 showed that each 10 µg/m -³ increase in daily concentrations of PM 2·5 was associated with increments of 0·27% in mortality from cardiovascular diseases, 0·30% from coronary heart diseases, and 0·23% from stroke. 95 Worsening air quality also contributes to increasing mortality from respiratory disease. It has been estimated that an increase of 10 000 tonnes of industrial SO 2 would increase mortality from respiratory diseases by 0·03 per 10 000 people in 116 prefectural-level cities, with spatial spillover effects leading to an increase in mortality of 1·54 per 10 000 people in neighbouring cities.…”
Section: Air Pollutionmentioning
confidence: 99%